S-Ketamine’s Effect Changes the Cortical Electrophysiological Activity Related to Semantic Affective Dimension of Pain: A Placebo- Controlled Study in Healthy Male Individuals - Schwertner, André; Zortea, Maxciel; Torres, Felipe Vasconcelos; Ramalho, Leticia; Alves, Camila Fernanda da Silveira; Lannig, Guilherme; Torres, Iraci L. S.; Fregni, Felipe; Gauer, Gustavo; Caumo, Wolnei (Frontiers in Neuroscience, 2019)
Background: Previous studies using the electroencephalogram (EEG) technique pointed out that ketamine decreases the amplitude of cortical electrophysiological signal during cognitive tasks, although its effects on the perception and emotional-valence judgment of stimuli are still unknown. Objective: We evaluated the effect of S-ketamine on affective dimension of pain using EEG and behavioral measures. The hypothesis was that S-ketamine would be more effective than placebo, both within and between groups, to attenuate the EEG signal elicited by target and non-target words. Methods: This double-blind parallel placebo-controlled study enrolled 24 healthy male volunteers between 19 and 40 years old. They were randomized to receive intravenous S-ketamine (n=12) at a plasmatic concentration of 60 ng/ml or placebo (n=12). Participants completed a computerized oddball paradigm containing written words semantically related to pain (targets), and non-pain related words (standard). The volunteers had to classify the words either as “positive,” “negative” or “neutral” (emotional valence judgment). The paradigm consisted in 6 blocks of 50 words each with a fixed 4:1 target/non-target rate presented in a single run. Infusion started during the interval between the 3rd and 4th blocks, for both groups. EEG signal was registered using four channels (Fz, Pz, Pz, and Oz, according to the 10-20 EEG system) with a linked-earlobe reference. The area under the curve (AUC) of the N200 (interval of 100-200ms) and P300 (300-500ms) components of event-related potentials (ERPs) was measured for each channel. Results: S-ketamine produced substantial difference (delta) in the AUC of grand average ERP components N200 (P=0.05) and P300 (P=0.02) at Pz during infusion period when compared to placebo infusion for both targets and non-targets. S-ketamine was also associated with a decrease in the amount of pain-related words judged as negative from before to after infusion [mean=0.83 (SD=0.09) vs. mean=0.73 (SD=0.11), respectively; P=0.04]. Conclusions: Our findings suggest that S-ketamine actively changed the semantic processing of written words. There was an increase in electrophysiological response for pain-related stimuli and a decrease for standard stimuli, as evidenced by the increased delta of AUCs. Behaviorally, S-ketamine seems to have produced an emotional and discrimination blunting effect for pain-related words.